Accelerated Life Test for Photovoltaic Cells Using Concentrated Light - Daniel Tudor Cotfas; Petru Adrian Cotfas; Dan Ion Floroian; Laura Floroian (International Journal of Photoenergy)
This paper presents a new method developed to significantly reduce the necessary time for the ageing tests for different types of photovoltaic cells. Two ageing factors have been applied to the photovoltaic cells: the concentrated light and the temperature. The maximum power of the photovoltaic cells was monitored during the ageing process. The electrical dc and ac parameters of the photovoltaic cells were measured and analyzed at 1 sun irradiance, before and after the test stress. During the test, two photovoltaic cells are kept at maximum power point and the other two are kept at open circuit voltage point. The method is validated through the results obtained for the monocrystalline silicon solar cell.